Barista-Quality Plant-Based Milk for Coffee: A Comprehensive Review of Sensory and Physicochemical Characteristics - Akansha Gupta; Russell Keast; Djin Gie Liem; Snehal R. Jadhav; Dipendra Kumar Mahato; Shirani Gamlath (Beverages)
The demand for plant-based milk alternatives (PMAs) has grown rapidly in recent years, driven by health-conscious choices, environmental sustainability, ethical considerations, and environmental concerns. Among these, “barista-quality” PMAs play a critical role in coffee applications. However, achieving the desired sensory attributes (flavour and mouthfeel) and physicochemical properties (texture, foam formation, and stability) of PMAs to closely resemble dairy milk in coffee remains a significant challenge. This review provides a comprehensive analysis of the sensory and physicochemical characteristics of PMAs, with a particular focus on their performance in hot coffee beverages such as cappuccinos and lattes. It examines the fundamental issues and factors influencing the compatibility of PMAs in hot coffee, including flavour, texture, foam formation and stability, and consumer acceptance. Furthermore, this review explores potential strategies to address these sensory and physicochemical challenges, offering valuable insights into opportunities for innovation and product development. The aim is to guide the optimization of next-generation “barista-quality” PMAs with improved sensory and functional properties.